Values Education in China: A Critical Discourse Analysis of the People’s Education Press’s Seventh Grade English Textbook - Wu, Lei; Wu, Lifu (Universitas Pendidikan Mandalika, 2025)
In the fall of 2024, the People’s Education Press (PEP) of China published the latest edition of its English as a foreign language (EFL) textbook for the first semester of seventh grade. This study conducted a content analysis of the EFL textbook for the first semester of seventh grade from the perspective of values. After content analysis, the researchers concluded that this EFL textbook includes two dimensions and five themes at the value level. Personal values include morality and identity, and social values include patriotism, collectivism, and cultural concepts. This study used critical discourse analysis to interpret the themes of content analysis. The researchers argued that patriotism, collectivism, Chinese culture, and the current state of education all influenced this EFL textbook. The researchers suggested that this EFL textbook should be further revised to be more diverse, inclusive, and critical. In addition, the researchers attached importance to the analysis of this EFL textbook from a global context perspective and suggested that global citizenship education should be included. This study provides corresponding suggestions for the compilation of EFL textbooks by PEP and education policymakers in China.